2009
DOI: 10.1111/j.1468-0084.2008.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sibship Size, Birth Order and Sex Composition on School Enrolment in Urban Turkey*

Abstract: This paper investigates, in a unified framework, the effects of sibship size, birth order and sibling sex composition on children's school enrolment in urban Turkey. We utilize an instrumental variable estimation method to address parents' joint fertility and schooling decisions using twin births as instruments. We find no causal impact of sibship size on school enrolment. However, there is evidence for a parabolic impact of birth order where middle-born children fare worse. Sex composition of siblings matters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Previous researchers have reported a relation between a child's birth order and well-being indicators, such as intellectual ability (Belmont and Marolla 1973;Steelman et al 1980Steelman et al , 2002Downey 1995Downey , 2001Kristensen and Bjerkedal 2007), educational attainment (Butcher and Case 1994;Steelman et al 2002;Dayioglu et al 2009) and health among young children (Horton 1986;Rosenzweig 1986;Das Gupta 1987;Behrman 1988;Amin 1990;Pande 2003). However, less attention has been paid to the role of sibling composition, or how the specific number of older or younger sisters and older or younger brothers might affect these outcomes.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous researchers have reported a relation between a child's birth order and well-being indicators, such as intellectual ability (Belmont and Marolla 1973;Steelman et al 1980Steelman et al , 2002Downey 1995Downey , 2001Kristensen and Bjerkedal 2007), educational attainment (Butcher and Case 1994;Steelman et al 2002;Dayioglu et al 2009) and health among young children (Horton 1986;Rosenzweig 1986;Das Gupta 1987;Behrman 1988;Amin 1990;Pande 2003). However, less attention has been paid to the role of sibling composition, or how the specific number of older or younger sisters and older or younger brothers might affect these outcomes.…”
Section: Introductionmentioning
confidence: 92%
“…Researchers in fields as diverse as economics (Butcher and Case 1994;Steelman et al 2002;Dayioglu et al 2009), anthropology (Hrdy 1992;Borgerhoff-Mulder 1998;Hagen and Barrett 2009;Kramer 2010) and evolutionary biology (Trivers 1972(Trivers , 1974Wilson 1984, 1988;Zeller 1987;Clutton-Brock 1991) have posed questions about how major life events such as the number of children in a household, age of first reproduction or level of parental investment (PI) shape the evolution of human families. Together, these studies constitute life-history research.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies focusing solely on education have found negative effects of a male cohort (Bommier and Lambert 2004;Dayioglu et al 2009;Kambhampati and Rajan 2008;Morduch 2000;Ota and Moffatt 2007;Parish and Willis 1993;Rammohan and Dancer 2008), effects on other composite outcomes, such as health and mortality, are ambiguous. Makepeace and Pal (2008) showed evidence of gender crowding out in India: boys with a more dominantly male sibship have higher mortality rates.…”
Section: Existing Evidence Of Cohort Effectsmentioning
confidence: 99%
“…Individuals can be considered altruistic if the larger the number of younger siblings is, the more they are likely to prefer income redistribution. Furthermore, the sex of siblings appears to be an important factor determining economic outcomes (Garg and Morduch 1998;Dayiogru et al 2009). To more closely examine the effect of experiencing competition in the family, siblings need to be divided into elder and younger siblings and then this effect can be examined.…”
Section: Further the First-born Person Among Siblings Is Less Likelymentioning
confidence: 99%
“…Kawaguchi and Miyazaki (2009) used data from Japan to test this argument and found that men raised by full-time working mothers are less likely to support traditional gender roles and are also less likely to believe in the negative effect of a mother working on her children's development. 3 It is widely acknowledged that family structure, such as birth order and the number of siblings, leads to different economic outcomes; for example, accumulation of human capital (e.g., Berman and Taubman, 1986;Kessler, 1991;Hanushek 1992;Oettinger 2000;Black et al 2005;Kantrevic and Mechoulan, 2006;Lee 2008;Dayiogru et al 2009;Dammert, 2010;Cho 2011;Buckles and Munnich 2012), participation in the labor market (Edmonds, 2006), child mortality (Makepeace and Pal 2008;Chamarbagwala, 2011), and inequality (Mazumder 2008). This might be partly because of large birth-order differences in the amount of quality lime that children spend with their parents (Price 2008).…”
Section: Introductionmentioning
confidence: 99%